Fatty acid profile of meat from European and Zebu bulls fed with pearl millet - Silva, Rodrigo Medeiros da; Restle, João; Missio, Regis Luis; Lage, Moacir Evandro; Pacheco, Paulo Santana; Bilego, Ubirajara Oliveira; Pádua, João Teodoro; Fausto, Daiane Aparecida (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the fatty acid profile of crossbreed steers, in confinement, fed with diets containing increasing levels of ground millet grain in replacement to ground corn grain. Twenty‑four European crossbred bulls and 24 Zebu crossbred bulls, slaughtered at 24 months of age, after 96 days in confinement, were used. The experimental design was completely randomized with treatments in a 4x2 factorial arrangement (four diets with 0, 33, 66, and 100% of pearl millet in the concentrate and two genetic groups) with six replicates. The increase in the levels of pearl millet grain in the diet increased linearly the participation of the arachidic (C20:0), heneicosanoic (C21:0), α‑linolenic (C18:3 n‑3), and dihomo‑γ‑linolenic (C20:3 n‑6) fatty acids. European bulls showed meat with lower content of myristic (C14:0), heneicosanoic (C21:0), and γ‑linolenic (C18:3 n‑6) fatty acids than the Zebu bulls. The total concentration of saturated (45.2%), monounsaturated (41.2%), and polyunsaturated (8.7%) fatty acids, and the monounsaturated/saturated (1.09) and polyunsaturated/saturated (0.18) ratio were not affected by the genetic groups and diets. The increase in the percentage of millet grain in the diet of European and Zebu bulls improves the ratio between ω‑6/ω‑3 fatty acids.
Keywords: Pennisetum americanum; saturated fatty acids; cattle; meat; CLA; linoleic